Bridging Institutional and Regulatory Gaps: Enhancing Sharia Compliance in Islamic Financial Institutions in Indonesia - Suaidi, Suaidi (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2025)
The compliance of Islamic Financial Institutions (LKS) with Islamic economic regulations is crucial for maintaining the stability and competitiveness of Indonesia's Islamic finance industry. Key regulations—such as Law No. 21 of 2008, OJK regulations, and DSN‑MUI fatwas—are designed to ensure that LKS operations adhere to Sharia principles. However, the implementation of these regulations faces several challenges, including regulatory harmonization, infrastructure readiness, and low levels of public Islamic financial literacy. This study employs a descriptive qualitative approach by analyzing the regulations and their implementation through legal document reviews, regulatory reports, and academic research. The findings indicate that the effectiveness of LKS compliance depends heavily on the role of the Sharia Supervisory Board (DPS), which often encounters issues of independence and competence. Furthermore, both employees' and customers' understanding of Islamic finance emerges as a key factor influencing regulatory adherence. Based on these results, this study recommends enhanced synergy among regulators, the industry, and the public to strengthen Sharia governance, boost DPS competence, and improve Islamic financial literacy. Such efforts are necessary to optimize regulatory compliance and enable the sustainable development of the Islamic finance industry.